Ramelteon for Prevention of Postoperative Delirium: A Randomized Controlled Trial in Patients Undergoing Elective Pulmonary Thromboendarterectomy*. Issue 12 (December 2019) - Jaiswal, Stuti J.; Vyas, Anuja D.; Heisel, Andrew J.; Ackula, Haritha; Aggarwal, Ashna; Kim, Nick H.; Kerr, Kim M.; Madani, Michael; Pretorius, Victor; Auger, William R.; Fernandes, Timothy M.; Malhotra, Atul; et al.
Abstract : Objectives: To assess the efficacy of ramelteon in preventing delirium, an acute neuropsychiatric condition associated with increased morbidity and mortality, in the perioperative, ICU setting. Design: Parallel-arm, randomized, double-blinded, placebo-controlled trial. Setting: Academic medical center in La Jolla, California. Patients: Patients greater than or equal to 18 years undergoing elective pulmonary thromboendarterectomy. Interventions: Ramelteon 8 mg or matching placebo starting the night prior to surgery and for a maximum of six nights while in the ICU. Measurements and Main Results: Incident delirium was measured twice daily using the Confusion Assessment Method-ICU. The safety outcome was coma-free days assessed by the Richmond Agitation-Sedation Scale. One-hundred twenty participants were enrolled and analysis completed in 117. Delirium occurred in 22 of 58 patients allocated to placebo versus 19 of 59 allocated to ramelteon (relative risk, 0.8; 95% CI, 0.5–1.4; p = 0.516). Delirium duration, as assessed by the number of delirium-free days was also similar in both groups (placebo median 2 d [interquartile range, 2–3 d] vs ramelteon 3 d [2–5 d]; p = 0.181). Coma-free days was also similar between groups (placebo median 2 d [interquartile range, 1–3 d] vs ramelteon 3 d [2–4 d]; p = 0.210). We found no difference in ICU length of stay (median 4 d [interquartile range, 3–5 d] vs 4 d [3–6 d]; p = 0.349), or in-hospital mortality (four vs three deaths; relative risk ratio, 0.7; 95% CI, 0.2–3.2; p = 0.717), all placebo versus ramelteon, respectively. Conclusions: Ramelteon 8 mg did not prevent postoperative delirium in patients admitted for elective cardiac surgery. Abstract : Supplemental Digital Content is available in the text.